The other as a reflection of his own ideal ego? Considerations on the criticism of Todorov in Montaigne - Fiucci, Adamas (Itinerari, 2023)
This article aims to examine Tzvetan Todorov’s controversial critique of Michel de Montaigne as a precursor of anti-colonialism. His position – according to which the French author is an egotist, not able to approach cultural diversity – shows the inconsistency in the moral theory presented in the “Essais,” accused of being based on the illogical coexistence of relativism (man is a result of custom) and universalism (man can grasp what is true, good and right). But Todorov comes to this conclusion because he has omitted those propositions of Montaigne’s from which, on the contrary, coherent ethical theory emerges. If we restart by refuting this ontological misunderstanding, it will then be possible both to reveal Montaigne’s true vision of otherness and to rediscuss his affinity with post-colonial semantics.